Методика визначення ефективності використання машин та механізмів в будівельному виробництві - Доненко, І. В.; Бобраков, А. А.; Тимощук, Д. В. (Ways to Improve Construction Efficiency, 2013)
The paper proposed a method for determining the effectiveness of mechanization in the construction of which is based on the requirements that characterize the impact of new machines to increase the technical and economic indices of construction, including productivity growth, the release of workers, cost of labor, material and energy resources, and others. And improving the quality of work.